(untitled) (Far Eastern Federal University: School of Engineering Bulletin, 2023)
Comprehensive restoration of the territory of cities is necessary after the destructive impact of the construction and economic activities of man, as a result of natural disasters, and also as a result of explosions. The article deals with the issues of integrated development of the port of Beirut (Lebanon).The study is based on the methods of cartographic analysis and on the SWOT method. As a result of the study of the territory, potential opportunities and threats, strengths and weaknesses of the port were identified. The result of the work is the development of principles for the development of the port area, taking into account national identity, the need to develop a natural framework, and Lebanon’s integration into the global tourism economy.